Protection of the Rights of All Migrant Workers and Members of Their Families Within the Albanian Context - Peka, Nejla (European Journal of Multidisciplinary Studies, 2017)
The purpose of this exploratory study is to investigate about the changes in legal framework and the role that legislative measures play in promoting and protecting all the people rights, especially of all migrant workers and members of their families. The study employs a mixed methodology, comprising a review of the legislation, institutional framework, statistics data and some of the relevant literature in the field of international law, regarding the conventions, bilateral agreements and some other documents for promoting and respecting migrant workers’ rights. The findings of this study are supported in prior research in analyzing a lot of documents, strategies, prepared by NGO-s and other government institutions. The in-depth analysis of the qualitative data revealed a basic understanding of promoting and protecting migrant workers and members of their families in my country.
Keywords: international law, social cohesion, migration, migrant worker, work, education, social protection, promoting and protecting migrant worker’s rights, legal framework etc.